PENGARUH LOCUS OF CONTROL DAN ROLE AMBIGUITY TERHADAP EFEKTIVITAS KERJA ANGGOTA DIREKTORAT LALU LINTAS (DIRLANTAS) KEPOLISIAN DAERAH LAMPUNG - Heti Patmawati dan Novi Indah Earlyanti Heti Patmawati dan Novi Indah Earlyanti (Universitas Lampung, 2014)
Objectives to be achieved in this paper is to investigate the influence of locus of control, and role ambiguity on the effectiveness of the members in Lampung Police Ditlantas. The approach used is a quantitative by using survey method, which involves total population of 179 people and sample 119 people, 14 of them were not present, so that only 105 people as samples. Data collection techniques using questionnaires. Data analysis techniques using a test instrument (validity and reliability), the classic assumption test and test hypotheses. Based on the findings of research and discussion, conclusions: (1) the influence of locus of control is a positive and significant on the effectiveness of members' work; (2) the effect of role ambiguity is significant to the effectiveness of members' work; and (3) the influence of locus of control and role of ambiguity is significant to the effectiveness of members' work. It is therefore recommended: (1) that the parties of organization or management making methods / guidelines are very clear for members, so members are not confused about what the organization wishes to members regarding their performance, (2) role ambiguity can be eliminated with the organizational structure along with a clear job description, giving a clear task information, so that members not only to fumble on the description of each task.Keywords: Locus of Control, Role Ambiguity, work effectiveness